Projeto Guaná IA: inovação no ensino de línguas em risco - Ortiz Coronel, Derlis (2024)
This research paper addresses the situation of the Guaná language in Paraguay, one of the indigenous peoples of the Maskoy linguistic family, highlighting the challenges and opportunities for its revitalization through artificial intelligence. Among the main justifications is that the Guaná language faces a serious threat of extinction, with only three elderly native speakers, which requires comprehensive measures for its preservation. The objective of the paper is to analyze the proposal for the integration of artificial intelligence in an educational curriculum for  the revitalization of the Guaná language. The methodology was based on a literature review and comparative case studies of language revitalization in similar contexts. As for the results, effective strategies for language documentation and teaching were identified, including the use of digital tools and the creation of adaptive educational resources. The conclusion is that artificial intelligence, combined with culturally relevant educational approaches, can play a key  role in language preservation, promoting its  intergenerational use and transmission.